2007
DOI: 10.1083/jcb.200608109
|View full text |Cite
|
Sign up to set email alerts
|

Critical requirement for cell cycle inhibitors in sustaining nonproliferative states

Abstract: In adult vertebrates, most cells are not in the cell cycle at any one time. Physiological nonproliferation states encompass reversible quiescence and permanent postmitotic conditions such as terminal differentiation and replicative senescence. Although these states appear to be attained and maintained quite differently, they might share a core proliferation-restricting mechanism. Unexpectedly, we found that all sorts of nonproliferating cells can be mitotically reactivated by the sole suppression of histotype-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
92
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 57 publications
13
92
0
2
Order By: Relevance
“…It is of note that although the levels of this cyclin-dependent kinase inhibitors decrease, it is required for maintaining the post-mitotic state of myotubes. 19 The apoptosis protease-activating factor 1 (Apaf-1) is progressively downregulated in post-mitotic muscle cells. The decrease in Apaf-1 of myotubes has been associated with their resistance to apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…It is of note that although the levels of this cyclin-dependent kinase inhibitors decrease, it is required for maintaining the post-mitotic state of myotubes. 19 The apoptosis protease-activating factor 1 (Apaf-1) is progressively downregulated in post-mitotic muscle cells. The decrease in Apaf-1 of myotubes has been associated with their resistance to apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that this state is readily and rapidly reversed by inactivating the oncogenic stimulus in combination with the transient knockdown of p16 and p21. Likewise, the cell-cycle exit of replicatively senescent human cells or terminally differentiated myotubes is readily reversed by CKI knockdown (Beausejour et al, 2003;Pajalunga et al, 2007). The senescent state thus appears to depend on a dynamic regulatory network that must be actively maintained in order to prevent reversion.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that there are also reports in the literature indicating that different forms of senescence might be reversible. For instance, a previous study demonstrated that non-proliferating cells can be mitotically reactivated by the sole suppression of cyclin-dependent kinase inhibitors (CKIs) in the absence of exogenous mitogens (Pajalunga et al, 2007). RNA interference-mediated suppression of CKIs efficiently triggered mitosis in terminally differentiated skeletal muscle cells, quiescent fibroblasts and senescent embryo kidney cells.…”
Section: Downregulation Of Tacc3 Induces Cellular Senescence S Schmidmentioning
confidence: 99%